Незмінність прокурора у кримінальному провадженні - Крикунов О.; Денісова Г.; Krykunov O.; Denisova G. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
З’ясовано історико-правовий аспект, зміст, функціональне навантаження норми про незмінність прокурора у кримінальному процесі. Визначено суб’єктів та період кримінального провадження, на які поширює дію норма про незмінність прокурора. Окреслено сукупність законних підстав для заміни прокурора, найбільш неоднозначні із яких піддано аналізу. Встановлено причини недотримання норми про незмінність прокурора; сформульовано науково обгрунтовані пропозиції для удосконалення чинного КПК та практики його застосування. The article highlights the issues of legal support and scientific approaches to the irremovability of the prosecutor in criminal proceedings. The irremovability of the prosecutor as a legal and functional feature of his status in criminal proceedings ensures his independence, efficiency, and at the same time, personifies his responsibility. A systematic analysis of the provisions of the Criminal Procedure Code (CPC) of Ukraine on the participation of the prosecutor in criminal proceedings indicates the existence of a significant number of grounds for the replacement of the prosecutor, which require specification in in part of evaluative notions. Some grounds for replacing a prosecutor are discretionary, which creates risks of errors in their application. The ground for replacing a prosecutor in criminal proceedings, which reads «other valid reasons that make it impossible for a prosecutor to participate in criminal proceedings» (Part 3 of Article 37 of the CPC of Ukraine), is quite discretionary. It should be supplemented with the statement «confirmed by specific facts that prove them» for correct use
Irremovability of the Prosecutor in Criminal Proceedings
Keywords: прокурор; незмінність; кримінальне провадження; prosecutor; irremovability; criminal proceedings